Towards Standardisation of Bioprinting - Martín Compaired, Pablo; García Gareta, Elena; Pérez, María Ángeles (Jornada de Jóvenes Investigadores del I3A, 2025)
Bioprinting is an emerging technology in biomedical fields such as tissue engineering; however, its recent adoption has resulted in a lack of standardised protocols. This work proposes a methodology to streamline the bioprinting process and enhance print quality, addressing current challenges in consistency and reproducibility.